GENDER BASED VIOLENCE STILL UNDER FIRE. THE ISTANBUL CONVENTION AND THE ROMANIAN WAY - Diana Elena NEAGA (Challenges of the Knowledge Society)
Romania ratified the Istanbul Convention on 23 May 2016, and this can be considered a very important moment in the history of fighting gender-based violence. The Istanbul Convention is considered to be the most far-reaching international treaty addressing violence against women and domestic violence by offering a detailed and comprehensive set of provisions together with important and overarching preventive and protective measures in fighting these phenomena. Nevertheless, there are voices openly criticizing the Convention and advocate for different countries to withdraw from the international agreement. Given the abovementioned context, in my article I will first try to make an analysis of the arguments that made the Convention into the gold standard in protecting women and girls’ rights. Secondly, I will briefly present how and why this “gold standard” has been contested. Last but not least, using the document analysis method, I will attempt a critical review of the way in which Romania responded to the Istanbul Convention requirements, underlining the most important conceptual and legal developments/adjustments that have been done.